Measuring the Financial Performance of Village Owned Enterprises (VOEs) - Sari, Yuni Purwita (JPAS (Journal of Public Administration Studies), 2019)
In order to accommodate village potentials and fulfillment of villagers’ needs, through Law No. 32 of 2004 concerning Local Government, the government provides great support so that the village has a business entity which is able to develop and drive the local economy. Law No. 32 0f 2004 states that the village can establish a village-owned enterprises (VOEs), village businesses formed / established by the village government whose capital ownership and management are carried out by the village government and the community, in accordance with the needs and potential of the village. In its development, VOEs were encouraged as economic institutions at the village level supported by the government in order to handle economic activities at the village level because their shares were dominated by the village government. In the framework of this achievement, the financial performance assessment is needed to give feedback for VOEs manager in making the right decision for VOEs development. This study aims to search a proper measurement that appropriate to measure the financial performance of Village Owned Enterprises (VOEs). The result of the study found that several financial ratios can be utilized to measure the financial performance of Village Owned Enterprises (VOEs). Those financial ratios can be classified into capital, asset, management, earning and liquidity assessment, which is known as CAMEL model:1) Ratio of Asset Development is used to measure the Capital Adequacy; 2) Ratio of Productive Asset Quality is used to measure the Asset Quality; 3)BoPo Ratio (Operational Cost of Operating Income) is used to measure the Management Efficiency; 4) Ratio on Asset (ROA) is used to measure the Earnings Quality; and 5)Loan to Deposit Ratio to measure the Liquidity.